Answer:
Explanation:
1 Simplify (-3,5)y(−3,5)y to -3,5y−3,5y.
-3,5y=\frac{2}{3}x+1
−3,5y=
3
2
x+1
2 Simplify \frac{2}{3}x
3
2
x to \frac{2x}{3}
3
2x
.
-3,5y=\frac{2x}{3}+1
−3,5y=
3
2x
+1
3 Switch sides.
\frac{2x}{3}+1=-3,5y
3
2x
+1=−3,5y
4 Break down the problem into these 2 equations.
\frac{2x}{3}+1=-3
3
2x
+1=−3
\frac{2x}{3}+1=5y
3
2x
+1=5y
5 Solve the 1st equation: \frac{2x}{3}+1=-3
3
2x
+1=−3.
x=-6
x=−6
6 Solve the 2nd equation: \frac{2x}{3}+1=5y
3
2x
+1=5y.
x=\frac{3(5y-1)}{2}
x=
2
3(5y−1)
7 Collect all solutions.
x=-6,\frac{3(5y-1)}{2}
x=−6,
2
3(5y−1)